2014
DOI: 10.1155/2014/416409
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of Ethanolic Extract ofCurcuma xanthorrhizaLeaf against Ethanol-Induced Gastric Mucosal Lesions inSprague-DawleyRats

Abstract: Herbal medicines appeared promising in prevention of many diseases. This study was conducted to investigate the gastroprotective effect of Curcuma xanthorrhiza leaf in the rats induced gastric ulcer by ethanol. Normal and ulcer control received carboxymethycellulose (5 mL/kg) orally, positive control was administered with 20 mg/kg omeprazole (reference drug) and 2 groups were received 250 mg/kg and 500 mg/kg of the leaf extract, respectively. To induce of gastric ulcers formation, ethanol (5 mL/kg) was given o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 46 publications
3
25
0
2
Order By: Relevance
“…Thus, the bicarbonate secretion was reduced while mucus production was increased. In the histological evaluation, acute ulcers were characterized by the presence of hemorrhage, necrosis and granulation tissue, while the chronic ulcers show the presence of granulation tissue at the base and disruption of muscularis propria (Rahim et al, 2014). Histological results of the present study confirm the severe microscopic damages to the mucosal layer caused by ethanol.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the bicarbonate secretion was reduced while mucus production was increased. In the histological evaluation, acute ulcers were characterized by the presence of hemorrhage, necrosis and granulation tissue, while the chronic ulcers show the presence of granulation tissue at the base and disruption of muscularis propria (Rahim et al, 2014). Histological results of the present study confirm the severe microscopic damages to the mucosal layer caused by ethanol.…”
Section: Discussionsupporting
confidence: 69%
“…20 Catalase and SOD are essential to the body in order to discharge the harmful ROS from the cellular environment. 21 The present study showed that mean SOD and catalase levels were significantly increased in extract treated-500 group-III, extract treated-1000 group-IV and standard drug treated group-V as compared to that decreased in ulcer control group-II rats. HEPB is free from toxic substances and is a safe source of antioxidants.…”
Section: Discussionsupporting
confidence: 44%
“…HEPB is free from toxic substances and is a safe source of antioxidants. 21 These results suggested the possible involvement of endogenous antioxidants in the experimental effect of HEPB in gastric ulcer. The gastroprotective effect of HEPB could be due to the presence of phenolics present in the extract which was found to be 4378 µg GAE/ g dried extract of HEPB as phenolics possess antioxidant potential.…”
Section: Discussionmentioning
confidence: 86%
“…However, among the different traditional Malaysian plants (Polygonum minus, Andrographis paniculata, Curcuma xanthorrhiza, Momordica charantia and Strobilanthes crispus), Polygonum minus has potentially better inhibition percentage on ulcer area. Another study showed the antiulcer activity of Curcuma xanthorrhiza ethanolic leaf extract against ethanol-induced gastric ulcerative lesions in rats (Rahim et al, 2014).…”
Section: Curcuma Xanthorrhizamentioning
confidence: 99%